A high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film material and preparation method thereof

By constructing a polymer framework in a polymer matrix with high melt viscosity and inhaling a boron nitride dispersion to form a hexagonal boron nitride/polyphenylsulfone/polyether etherketone composite film material with a bicontinuous phase structure, the problem of insufficient thermal conductivity of the existing composite materials is solved and the improvement of high thermal conductivity is achieved.

CN115746499BActive Publication Date: 2025-04-01WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211332975.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-28
Publication Date
2025-04-01
Estimated Expiration
2042-10-28

AI Technical Summary

Technical Problem

Existing polymer composite materials have limitations in improving thermal conductivity, especially in polymer matrix with high melt viscosity, it is difficult to form effective thermal conductivity paths, which cannot meet the high thermal conductivity needs in electronics and electrical fields.

Method used

Hexagonal boron nitride/polyphenylsulfone/polyether etherketone composite film material is used to first construct the polymer skeleton, and then suck the boron nitride dispersion into the skeleton in a vacuum environment to form a bicontinuous phase structure to improve thermal conductivity.

Benefits of technology

The thermal conductivity path is achieved in polymer matrix with high melt viscosity, which significantly improves the thermal conductivity of composite materials and broadens its application range in the field of thermally conductive composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003913817110000091
    Figure BDA0003913817110000091
  • Figure BDA0003913817110000101
    Figure BDA0003913817110000101
Patent Text Reader

Abstract

The present invention discloses a high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film, which comprises the following weight percentage components: 5-20wt% boron nitride, polyetheretherketone+polyphenylsulfone 80-95wt%. The present invention also discloses a preparation method of a high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film material, which has a simple process, easy-to-control conditions, and is easy to industrialize. The present invention realizes the formation of a heat conduction path in a polymer matrix with a high melt viscosity by utilizing a two-phase structure formed by melt blending of two polymers. According to the description of the embodiments, the hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film of the present invention has good thermal conductivity, which greatly broadens the application scope of high melt viscosity polymers in the field of thermal conductive composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal conductive composite materials, and in particular relates to a high thermal conductive hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film and a preparation method thereof. Background Art

[0002] With the continuous development of the electrical field, electronic devices are gradually showing a trend of miniaturization, and the continuous increase in the power density of electronic devices has also caused their heat generation to increase sharply. The resulting heat accumulation will affect the working efficiency of electronic devices, and in severe cases will even cause irreparable damage to them. Therefore, polymer materials with high thermal conductivity are increasingly attracting attention. However, the intrinsic thermal conductivity of most polymers is low, and high thermal conductivity fillers are required to improve their thermal conductivity. Commonly used thermal conductive fillers include metal powders, metal oxides, nitrides and carbon-based fillers. Among them, hexagonal boron nitride (h-BN), known as "white graphite", has ultra-high thermal conductivity and good stability. Compared with metal fillers, hexagonal boron nitride also has good insulation, which establishes its advantages in the field of insulating electrical appliances.

[0003] Polyetheretherketone (PEEK) is a special engineering plastic with extremely excellent performance. It has good chemical corrosion resistance, high heat resistance and mechanical strength. Therefore, PEEK resin is widely used in aerospace, electronics and electrical fields. At the same time, PEEK is a crystalline engineering plastic. Compared with amorphous polymers, it has a higher thermal conductivity and better high temperature resistance. In addition to polyetheretherketone, polyphenylsulfone (PPSU) is also a special engineering plastic with excellent performance. It has a high glass transition temperature, strong impact resistance, and good chemical stability. It is widely used in aerospace, electronics, biomedicine and other fields.

[0004] At present, most of the polymer composite materials on the market are prepared by physical blending methods, and their thermal conductivity is limited and still at a low level. Even if various interface modifiers are used to improve the distribution of fillers, the improvement of their thermal conductivity cannot meet people's needs, so there is an urgent need to innovate filling methods. The most effective idea is to allow thermally conductive fillers to overlap each other and form a path inside the matrix, so that the heat flow is transmitted in the thermally conductive filler, reducing phonon scattering and greatly improving its thermal conductivity. Some studies have tried to use technologies such as the ice film plate method to prepare composite materials by first preparing a thermally conductive filler skeleton and then filling it with polymers. However, for special engineering plastics such as polyetheretherketone, this method is not applicable because of their high melting point and high melt viscosity. Therefore, how to form a thermal conductive path in a polymer matrix with high melt viscosity has always been a difficult problem that has troubled people. Summary of the invention

[0005] The object of the present invention is to provide a high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film material and a preparation method thereof, wherein the composite film realizes the formation of a thermal conductive path in a polymer matrix with a high melt viscosity, thereby having excellent thermal conductivity. The preparation method of the present invention has a simple process, easily controllable conditions, and is convenient for large-scale automated production.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film material, which comprises:

[0008] Polyetheretherketone + polyphenylsulfone 80~95wt%

[0009] Hexagonal boron nitride 5-20wt%.

[0010] Preferably, the polyetheretherketone has a reduced viscosity of 0.8 to 1.0 dL / g and a glass transition temperature of 142 to 144°C.

[0011] Preferably, the polyphenylsulfone has a reduced viscosity of 0.5 to 0.7 dL / g and a glass transition temperature of 220 to 223°C.

[0012] When preparing the composite membrane material, the ratio of polyetheretherketone to polyphenylsulfone is preferably 1:1-2, more preferably 1:1.5.

[0013] Preferably, the particle size of the hexagonal boron nitride is 5 to 50 μm.

[0014] The present invention also provides a method for preparing the high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film material described in the above technical solution, comprising the following steps:

[0015] (1) mixing boron nitride preferably having a particle size of 5 to 50 μm with a dispersant, and subjecting the mixture to ultrasonic dispersion to obtain a boron nitride dispersion;

[0016] (2) blending polyetheretherketone and polyphenylsulfone powder, and then extruding and hot pressing to form a polymer film; immersing the polymer film in an organic solvent for etching, then washing away the solvent on the film after etching, and drying, preferably at 120 to 150° C. for 6 to 10 hours to obtain a polyetheretherketone skeleton;

[0017] (3) Dropping the boron nitride dispersion obtained in step (1) on the polyetheretherketone skeleton to evenly cover it, and then placing it in a vacuum environment for 4 to 6 hours. The boron nitride dispersion will be absorbed into the polymer skeleton by capillary action, and drying is preferably carried out in a vacuum oven at 100 to 120° C. for 1 to 2 hours, and hot pressing it into a thin film to obtain a high thermal conductivity hexagonal boron nitride-polyphenylsulfone-polyetheretherketone composite film material.

[0018] As a preferred solution, the following steps are included:

[0019] (1) Preparation of boron nitride dispersion: Boron nitride with a particle size of 5 to 50 μm is mixed with a certain mass of a dispersant, and ultrasonic dispersion treatment is performed using a 10KHZ ultrasonic rod for 5 to 15 hours to obtain a boron nitride dispersion.

[0020] (2) Preparation of polyetheretherketone skeleton: Polyetheretherketone and polyphenylsulfone are powder-blended in a certain mass ratio by a high-speed mixer, and then the blended powder is extruded into strips by a twin-screw extruder. The long strips are then made into short strips with a length of 2-10 cm and arranged in parallel, and then pressed into a polymer film by a hot press. The polymer film is soaked in an organic solvent for 1-2 days and etched. The treated film is washed with water or ethanol for 5-8 times, and after washing off the solvent, it is dried in an oven at 120-150°C for 6-10 hours to obtain a polyetheretherketone skeleton.

[0021] (3) Spread the polyetheretherketone skeleton obtained in step (2) on a glass plate in a vacuum oven, and then drop the boron nitride dispersion obtained in step (1) on the polyetheretherketone skeleton to evenly cover it, and then place it in a vacuum environment for 4 to 6 hours. The boron nitride solution will be absorbed into the polymer skeleton by capillary action. Dry it in a vacuum oven at 100 to 120°C for 1-2 hours, and after removing the solvent, the boron nitride will adhere to the skeleton. Finally, the polyetheretherketone skeleton adsorbed with boron nitride is pressed into a film in a hot press to obtain a high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite membrane material.

[0022] The method for preparing the boron nitride dispersion uses a dispersant that is an organic solvent that matches the surface energy of boron nitride, including one or more of isopropanol, ethanol and methanol, and the amount used is 15 to 25 times the mass of the boron nitride.

[0023] In the preparation method of the polyetheretherketone skeleton, in step (2), the extrusion temperature of the twin-screw extruder is 360-380°C, and the rotation speed is 30-50 r / min. The setting temperature of the hot press is 360-380°C, and the pressure is 10-15 MPA. The mass ratio of the polyetheretherketone to the polyphenylsulfone is 1:1-2, preferably 1:1.5.

[0024] In the preparation method of the polyetheretherketone skeleton, the organic solvent used for etching is one or more of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide, and the amount used is 5-10 times the mass of the polymer film.

[0025] In the preparation method of the hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite membrane material, in step (3), the hot pressing temperature is 340-350° C. and the pressure is 10-12 MPa.

[0026] The heat-conductive hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film of the present invention can be used in the fields of electronics and electrical, automobile energy and aerospace.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The process of the present invention is simple, the conditions are easy to control, and it is convenient for large-scale automated production.

[0029] (2) The present invention constructs a polymer skeleton in advance, controls the skeleton morphology, and then fills the filler into the polymer skeleton to form a dual-continuous phase structure. The thermal conductivity of the composite material prepared by this method is significantly improved compared with the direct blending method.

[0030] (3) Polyetheretherketone and polyphenylsulfone are two incompatible special engineering plastics. The present invention cleverly utilizes the two-phase structure formed by melt blending of the two polymers, and uses boron nitride as filler after etching to prepare an insulating high thermal conductive composite material with a dual continuous phase structure, thereby achieving the formation of a thermal conductive path in a high melt viscosity polymer matrix, greatly broadening its application range in the field of thermal conductive composite materials. DETAILED DESCRIPTION

[0031] Example 1

[0032] (1) Preparation of boron nitride dispersion: 1 g of boron nitride with a particle size of 5 to 50 μm was mixed with 25 mL of isopropyl alcohol (IPA) solution, and ultrasonic dispersion was performed using a 10 KHZ ultrasonic rod for 5 hours to obtain a boron nitride dispersion.

[0033] (2) Preparation of polyetheretherketone skeleton: Add 8g polyetheretherketone and 12g polyphenylsulfone powder into a high-speed mixer, stir at high speed for 5 minutes to mix evenly, then add it to a twin-screw extruder, extrude it into strips at a temperature of 360°C and a rotation speed of 30r / min, and then make the long strips into short strips with a length of 2cm. Arrange the short strips in parallel and place them in a hot press mold, and press them into a polymer film at a temperature of 360°C and a pressure of 15MPA. Soak the polymer film in NMP with a mass of 5 times its mass for 1 day for etching. Wash the treated film with ethanol 6 times, wash off the solvent and dry it in an oven at 120°C for 10 hours to obtain a polyetheretherketone skeleton.

[0034] (3) The polyetheretherketone skeleton obtained in step (2) is spread flat on a glass plate in a vacuum oven, and the boron nitride-isopropanol solution obtained in step (1) is dripped on the polyetheretherketone skeleton to make it evenly covered, and then placed in a vacuum environment for 4 hours. The boron nitride solution will be absorbed into the polymer skeleton by capillary action. Drying is carried out at 100°C in a vacuum oven for 2 hours. After removing the solvent, the boron nitride will adhere to the skeleton. Finally, the polyetheretherketone skeleton film adsorbed with boron nitride is placed in a hot press and hot pressed into a film at 340°C and 12MPA to obtain a hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite membrane material.

[0035] Example 2

[0036] (1) Preparation of boron nitride dispersion: 1.6 g of boron nitride with a particle size of 5 to 50 μm was mixed with 30 mL of isopropyl alcohol (IPA) solution, and ultrasonic dispersion was performed using a 10 KHZ ultrasonic rod for 10 hours to obtain a boron nitride dispersion.

[0037] (2) Preparation of polyetheretherketone film: Add 8g of polyetheretherketone and 8g of polyphenylsulfone to a high-speed mixer, stir at high speed for 5 minutes to mix evenly, then add them to a twin-screw extruder, extrude them into strips at a temperature of 370°C and a speed of 40r / min, and then make the long strips into short strips with a length of 5cm. Arrange the short strips in parallel and place them in a hot press mold, and press them into a polymer film at a temperature of 370°C and a pressure of 12MPA. Soak the polymer film in DMF of 8 times its mass for 1 day for etching. Wash the treated film with ethanol 6 times, wash off the solvent, and dry it in an oven at 125°C for 8 hours to obtain a polyetheretherketone skeleton.

[0038] (3) Spread the polyetheretherketone skeleton obtained in step (2) on a glass plate in a vacuum oven, and then drop the boron nitride-isopropanol solution obtained in step (1) on the polyetheretherketone skeleton to evenly cover it, and then place it in a vacuum environment for 5 hours. The boron nitride solution will be absorbed into the polymer skeleton through capillary action. Dry it in a vacuum oven at 110°C for 1.5 hours, and after removing the solvent, the boron nitride will adhere to the skeleton. Finally, place the polyetheretherketone skeleton film adsorbed with boron nitride in a hot press, and hot press it into a film at 340°C and 12MPA to obtain a hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite membrane material.

[0039] Example 3

[0040] (1) Preparation of boron nitride dispersion: 2.3 g of boron nitride with a particle size of 5 to 50 μm was mixed with 35 mL of isopropyl alcohol (IPA) solution, and ultrasonic dispersion was performed using a 10 KHZ ultrasonic rod for 12 hours to obtain a boron nitride dispersion.

[0041] (2) Preparation of polyetheretherketone skeleton: 8g polyetheretherketone and 16g polyphenylsulfone were added to a high-speed mixer, stirred at high speed for 5 minutes to mix evenly, and then added to a twin-screw extruder, extruded into strips at a temperature of 380°C and a rotation speed of 50r / min, and then the long strips were made into short strips with a length of 5cm. The short strips were placed in parallel in a hot press mold and pressed into a polymer film at a temperature of 370°C and a pressure of 12MPA. The polymer film was immersed in DMAC with a mass of 6 times its mass for 1 day and etched. The treated film was washed with water 6 times, and after washing away the solvent, it was dried in an oven at 120°C for 10 hours to obtain a polyetheretherketone skeleton.

[0042] (3) The polyetheretherketone skeleton obtained in step (2) is spread flat on a glass plate in a vacuum oven, and the boron nitride-isopropanol solution obtained in step (1) is dripped on the polyetheretherketone skeleton to make it evenly covered, and then placed in a vacuum environment for 5 hours. The boron nitride solution will be absorbed into the polymer skeleton by capillary action. Drying is carried out in a vacuum oven at 110°C for 1.5 hours. After removing the solvent, the boron nitride will adhere to the skeleton. Finally, the polyetheretherketone skeleton adsorbed with boron nitride is placed in a hot press and hot pressed into a thin film at 350°C and 10MPA to obtain a hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite membrane material.

[0043] Example 4

[0044] (1) Preparation of boron nitride dispersion: 3 g of boron nitride with a particle size of 5 to 50 μm was mixed with 45 mL of isopropyl alcohol (IPA) solution, and ultrasonic dispersion was performed using a 10 KHZ ultrasonic rod for 15 hours to obtain a boron nitride dispersion.

[0045] (2) Preparation of polyetheretherketone skeleton: Add 8g polyetheretherketone and 12g polyphenylsulfone into a high-speed mixer, stir at high speed for 5 minutes to mix evenly, then add them into a twin-screw extruder, extrude them into strips at a temperature of 370°C and a rotation speed of 40r / min, and then make the long strips into short strips with a length of 10cm. Arrange the short strips in parallel and place them in a hot press mold, and press them into a polymer film at a temperature of 380°C and a pressure of 10MPA. Soak the polymer film in DMSO for 1 day and perform etching treatment. Wash the treated film with ethanol 6 times, wash off the solvent, and dry it in an oven at 150°C for 6 hours to obtain a polyetheretherketone skeleton.

[0046] (3) Spread the polyetheretherketone skeleton obtained in step (2) on a glass plate in a vacuum oven, and then drop the boron nitride-isopropanol solution obtained in step (1) on the polyetheretherketone skeleton to evenly cover it, and then place it in a vacuum environment for 6 hours. The boron nitride solution will be absorbed into the polymer skeleton by capillary action. Dry it in a vacuum oven at 120°C for 1 hour, and after removing the solvent, the boron nitride will adhere to the skeleton. Finally, place the polyetheretherketone skeleton film adsorbed with boron nitride in a hot press, and hot press it into a film at 340°C and 10MPA to obtain a hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite membrane material.

[0047] Comparative Example 1

[0048] 1.06g of boron nitride and 18.94g of polyetheretherketone powder were added to a high-speed mixer, stirred at high speed for 5 minutes to mix evenly, and then added to a twin-screw extruder, extruded into strips at a temperature of 360°C and a rotation speed of 30r / min, and then the long strips were made into short strips with a length of 2cm. The short strips were arranged in parallel and placed in a hot pressing mold, and pressed into a polymer film at a temperature of 360°C and a pressure of 15MPA, and the hexagonal boron nitride / polyetheretherketone composite film material prepared by direct blending was obtained.

[0049] Comparative Example 2

[0050] 2.24g of boron nitride and 17.76g of polyetheretherketone powder were added to a high-speed mixer, stirred at high speed for 5 minutes to mix evenly, and then added to a twin-screw extruder, extruded into strips at a temperature of 370°C and a rotation speed of 40r / min, and then the long strips were made into short strips with a length of 5cm. The short strips were arranged in parallel and placed in a hot pressing mold, and pressed into a polymer film at a temperature of 370°C and a pressure of 12MPA, and the hexagonal boron nitride / polyetheretherketone composite film material prepared by direct blending was obtained.

[0051] Comparative Example 3

[0052] 3.14g of boron nitride and 16.86g of polyetheretherketone powder were added to a high-speed mixer, stirred at high speed for 5 minutes to mix evenly, and then added to a twin-screw extruder, extruded into strips at a temperature of 380°C and a speed of 50r / min, and then the long strips were made into short strips with a length of 5cm. The short strips were arranged in parallel and placed in a hot pressing mold, and pressed into a polymer film at a temperature of 370°C and a pressure of 12MPA, and the hexagonal boron nitride / polyetheretherketone composite film material prepared by direct blending was obtained.

[0053] Comparative Example 4

[0054] 3.9g of boron nitride and 16.1g of polyetheretherketone powder were added to a high-speed mixer, stirred at high speed for 5 minutes to mix evenly, and then added to a twin-screw extruder, extruded into strips at a temperature of 370°C and a speed of 40r / min, and then the long strips were made into short strips with a length of 10cm. The short strips were arranged in parallel and placed in a hot pressing mold, and pressed into a polymer film at a temperature of 380°C and a pressure of 10MPA, and the hexagonal boron nitride / polyetheretherketone composite film material prepared by direct blending was obtained.

[0055] Comparative Example 5

[0056] 3.9g of boron nitride, 14.1g of polyetheretherketone and 2g of polyphenylsulfone powder were added to a high-speed mixer, stirred at high speed for 5 minutes to mix evenly, and then added to a twin-screw extruder, extruded into strips at a temperature of 370°C and a speed of 40r / min, and then the long strips were made into short strips with a length of 10cm. The short strips were arranged in parallel and placed in a hot pressing mold, and pressed into a polymer film at a temperature of 380°C and a pressure of 10MPA, and the hexagonal boron nitride / polyetheretherketone / polyphenylsulfone composite membrane material prepared by direct blending was obtained.

[0057] Test Case

[0058] The actual weight percentage of boron nitride in the thermally conductive composite film materials described in Examples 1 to 4 was obtained by TGA test (Pyris ONE thermogravimetric analyzer). The results are shown in Table 1.

[0059] Table 1: Actual weight percentage of boron nitride in the thermally conductive composite film materials described in Examples 1 to 4

[0060] Example 1 Example 2 Example 3 Example 4 BN / wt% 5.3. 11.2 15.7 19.5

[0061] As described in Comparative Examples 1 to 5, according to the test results in Table 1, BN / PEEK film materials (Comparative Examples 1-4) obtained by direct blending with the same boron nitride weight percentage as in Examples 1 to 4 and BN / PEEK / PPSU film materials (Comparative Example 5) obtained by direct blending with the same boron nitride weight percentage as in Example 4 were prepared. According to the standard of GBT-22588, the thermal conductivity of the thermally conductive composite film materials obtained in Examples 1 to 4 and Comparative Examples 1 to 5 was tested, and the test results are shown in Table 2:

[0062] Table 2: Thermal conductivity of the thermally conductive composite film materials described in Examples 1 to 4 and Comparative Examples 1 to 5

[0063]

[0064]

[0065] From the data of Comparative Examples 4 and 5 in Table 2, it can be seen that under the same amount of boron nitride added, the thermal conductivity of the composite film without polyphenylsulfone in the matrix is ​​higher than that of the composite film containing a small amount of polyphenylsulfone. This is because polyetheretherketone is a crystalline polymer, and its intrinsic thermal conductivity is higher than that of amorphous polyphenylsulfone. Therefore, the results of Examples 1-4 and Comparative Examples 1-4 show that after the thermal conductive path is formed, the hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film material provided by the present invention has a higher thermal conductivity.

[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film, characterized in that: The steps include: (1) mixing boron nitride with a dispersant, and subjecting the mixture to ultrasonic dispersion treatment to obtain a boron nitride dispersion; (2) blending polyetheretherketone and polyphenylsulfone powder, and then extruding and hot pressing to form a polymer film; immersing the polymer film in an organic solvent for etching, then washing away the solvent on the film after etching, and drying to obtain a polyetheretherketone skeleton; (3) Drop the boron nitride dispersion obtained in step (1) on the polyetheretherketone skeleton to make it evenly covered, and then place it in a vacuum environment for 4 to 6 hours. The boron nitride dispersion will be absorbed into the polymer skeleton by capillary action, and then dried and hot-pressed into a film to obtain a high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite membrane material.

2. The preparation method according to claim 1, characterized in that The concentrated viscosity of the polyetheretherketone is 0.8-1.0 dL / g, and the glass transition temperature is 142-144°C; and / or the concentrated viscosity of the polyphenylsulfone is 0.5-0.7 dL / g, and the glass transition temperature is 220-223°C.

3. The preparation method according to claim 1 or 2, characterized in that: The dispersant used in step (1) is an organic solvent that matches the surface energy of boron nitride, including one or more of isopropanol, ethanol and methanol, and the amount used is 15 to 25 times the mass of boron nitride.

4. The preparation method according to claim 1, characterized in that: In step (1), the particle size of the boron nitride is 5 to 50 microns.

5. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the polyetheretherketone to polyphenylsulfone is 1:1-2.

6. The preparation method according to claim 5, characterized in that: The mass ratio of polyetheretherketone to polyphenylsulfone is 1:1.

5.

7. The preparation method according to claim 1, characterized in that: In step (2), a twin-screw extruder is used for extrusion, the extrusion temperature is 360-380° C., and the rotation speed is 30-50 r / min.

8. The preparation method according to claim 1, characterized in that: In step (2), the hot pressing temperature is 360-380° C. and the pressure is 10-15 MPa.

9. The preparation method according to claim 1, characterized in that: In step (2), the organic solvent used for etching is one or more of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide, and the amount used is 5-10 times the mass of the polymer film.

10. The preparation method according to claim 1, characterized in that: In step (2), the polyetheretherketone skeleton is obtained after drying at 120-150° C. for 6-10 hours.

11. The preparation method according to claim 1, characterized in that: In step (3), the hot pressing temperature is 340-350° C. and the pressure is 10-12 MPa.

12. The preparation method according to claim 1, characterized in that: In step (3), the drying is performed in a vacuum oven at 100-120° C. for 1-2 h.

13. A high thermal conductivity hexagonal boron nitride / polyphenylene sulfone / polyetheretherketone composite film prepared according to any one of claims 1 to 12, comprising the following components in weight percentage: 5-20wt% boron nitride, 80-95wt% polyetheretherketone+polyphenylene sulfone.

14. Application of the high thermal conductivity hexagonal boron nitride / polyphenylsulfone / polyetheretherketone composite film according to claim 13 in the fields of electronics, automotive energy and aerospace.

Citation Information

Patent Citations

  • Polyetherimide compositions, articles made therefrom, and method of manufacture thereof

    CN107109057A

  • Polyether-ether-ketone-based polymer alloy composite material, and preparation method and application thereof

    CN111269530A